Educational Pathways to Remote Employment in Isolated Communities. - Denkenberger, David; Way, Julia; Pearce, Joshua M. (Journal of Human Security (Librello Publishing House), 2015)
Those who live in isolated communities often lack reliable, skilled employment opportunities, which fundamentally undermines their human security. For individuals who wish to remain in their isolated communities for family, religious, philosophical or other reasons, their attachment to their communities creates a disincentive for higher education. This promotes low educational achievement, which in turn results in low socioeconomic status, lack of social mobility, and a generational cycle of poverty. The human misery that results from such a feedback loop is observed in isolated communities throughout North America, including aboriginal communities in Canada. Fortunately, maturation of information and communication technologies now offers individuals the potential to gain high-skilled employment while living in an isolated community, using both (i) virtual work/remote work and (ii) remote training and education. To examine that potential, this study: 1) categorizes high-skill careers that demand a higher education and are widely viable for remote work, 2) examines options for obtaining the required education remotely, and 3) performs an economic analysis of investing in remote education, quantifying the results in return on investment. The results show that the Internet has now opened up the possibility of both remote education and remote work. Though the investment in college education is significant, there are loans available and the return on investment is generally far higher than the interest rate on the loans. The results identified several particularly promising majors and dozens of high-income careers. The ability to both obtain an education and employment remotely offers the potential to lift many people living in isolated communities out of poverty, reduce inequality overall, and provide those living in isolated communities with viable means of employment security, which not only allows personal sustainability, but also the potential for personal growth.